Serum Activity Against G Protein–Coupled Receptors and Severity of Orthostatic Symptoms in Postural Orthostatic Tachycardia Syndrome. Issue 15 (4th August 2020) - Kharraziha, Isabella; Axelsson, Jonas; Ricci, Fabrizio; Di Martino, Giuseppe; Persson, Margaretha; Sutton, Richard; Fedorowski, Artur; Hamrefors, Viktor
Abstract : Background: Postural orthostatic tachycardia syndrome (POTS) is characterized by excessive heart rate increase on standing and orthostatic intolerance. Previous data indicate autoimmune involvement. We studied serum activity against G protein–coupled receptors in relation to symptoms in patients with POTS and controls using a commercial cell‐based assay. Methods and Results: Forty‐eight patients with POTS (aged 28.6±10.5 years; 44 women) and 25 healthy individuals (aged 30.7±8.6 years; 21 women) were included. The 10‐item Orthostatic Hypotension Questionnaire (OHQ) was completed by 33 patients with POTS and all controls. Human embryonic kidney 293 cells overexpressing one G protein–coupled receptor: adrenergic α1 receptor, adrenergic β2 receptor, cholinergic muscarinic type 2 receptor, and opioid receptor‐like 1 were treated with sera from all patients. Receptor response was analyzed using a β‐arrestin–linked transcription factor driving transgenic β‐lactamase transcription by fluorescence resonance energy transfer method. Receiver operating characteristic curves were constructed. G protein–coupled receptor activation was related to OHQ indices in linear regression models. Sera from patients with POTS activated all 4 receptors to a higher degree compared with controls ( P <0.01 for all). The area under the curve was 0.88 (0.80–0.97, P <0.001) combining all 4 receptors. Adrenergic α1 receptor activation associated with OHQ composite score (β=0.77 OHQ points per SD of activity, P =0.009) and with reduced tolerability for prolonged standing ( P =0.037) and walking for short ( P =0.042) or long ( P =0.001) periods. All 4 receptors were associated with vision problems ( P <0.05 for all). Conclusions: Our results indicate the presence of circulating proteins activating adrenergic, muscarinic, and nociceptin receptors in patients with POTS. Serum‐mediated activation of these receptors has high predictive value for POTS. Activation of adrenergic α1 receptor is associated with orthostatic symptoms severity in patients with POTS.